2014
DOI: 10.1590/1414-431x20133193
|View full text |Cite
|
Sign up to set email alerts
|

Lipoic acid, but not tempol, preserves vascular compliance and decreases medial calcification in a model of elastocalcinosis

Abstract: Vascular calcification decreases compliance and increases morbidity. Mechanisms of this process are unclear. The role of oxidative stress and effects of antioxidants have been poorly explored. We investigated effects of the antioxidants lipoic acid (LA) and tempol in a model of atherosclerosis associated with elastocalcinosis. Male New Zealand white rabbits (2.5-3.0 kg) were fed regular chow (controls) or a 0.5% cholesterol (chol) diet+104 IU/day vitamin D2 (vitD) for 12 weeks, and assigned to treatment with w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Parallel reading of images was performed with identical laser acquisition settings. Control samples were preincubated with superoxide dismutase-polyethylene glycol (PEG-SOD) (500 U/mL for 7 min) to confirm the fluorescent signal as due to superoxide production [ 34 ].…”
Section: Methodsmentioning
confidence: 99%
“…Parallel reading of images was performed with identical laser acquisition settings. Control samples were preincubated with superoxide dismutase-polyethylene glycol (PEG-SOD) (500 U/mL for 7 min) to confirm the fluorescent signal as due to superoxide production [ 34 ].…”
Section: Methodsmentioning
confidence: 99%
“…α-Lipoic acid (ALA) is made in the human body and is essential for aerobic metabolism and as a cofactor in several enzymatic reactions. There are no human studies of the effect of ALA on CV calcification but in mice with calcification from heart tissue injury, ALA lowered tissue damage and reduced calcification [ 146 ], while in rabbits it reduced aortic valve and medial calcification [ 121 , 147 ]. N -acetylcysteine (NAC) functions principally as a mucolytic agent and helps to increase endogenous glutathione levels.…”
Section: Antioxidantsmentioning
confidence: 99%
“…We identified five types of potential antioxidants with therapeutic effects against VC based on the literature search, including linalool 61 , lipoic acid 2224 , rosmarinic acid 63 , fermentation broth extracts from Actinobacteria 59 , and polysaccharide from Fuzi product 60 . Two (40%) of them have ROS scavenging ability, while the other three (60%) do not (Fig.…”
Section: Antioxidants From Natural Non-dietary Sourcesmentioning
confidence: 99%
“…Several groups have proposed that lipoic acid could substantially attenuate VC in vitro and in vivo. Liberman et al showed that lipoic acid ameliorated aortic calcification and improved vascular compliance in high cholesterol- and vitamin D-fed rabbits by inhibiting Nox4 expression and reducing ROS 22,24 . Similar to quercetin, lipoic acid exhibited a beneficial effect against VC by improving mitochondrial function and inhibiting apoptosis, through restoring Gas6/Axl survival signaling 23 .…”
Section: Antioxidants From Natural Non-dietary Sourcesmentioning
confidence: 99%
See 1 more Smart Citation